Mobile Apps for Suicide Prevention: Review of Virtual Stores and Literature - de la Torre, Isabel; Castillo, Gema; Arambarri, Jon; López-Coronado, Miguel; Franco, Manuel A (JMIR Publications, 2017)
BackgroundThe best manner to prevent suicide is to recognize suicidal signs and signals, and know how to respond to them. ObjectiveWe aim to study the existing mobile apps for suicide prevention in the literature and the most commonly used virtual stores. MethodsTwo reviews were carried out. The first was done by searching the most commonly used commercial app stores, which are iTunes and Google Play. The second was a review of mobile health (mHealth) apps in published articles within the last 10 years in the following 7 scientific databases: Science Direct, Medline, PsycINFO, Embase, The Cochrane Library, IEEE Xplore, and Google Scholar. ResultsA total of 124 apps related to suicide were found in the cited virtual stores but only 20 apps were specifically designed for suicide prevention. All apps were free and most were designed for Android. Furthermore, 6 relevant papers were found in the indicated scientific databases; in these studies, some real experiences with physicians, caregivers, and families were described. The importance of these people in suicide prevention was indicated. ConclusionsThe number of apps regarding suicide prevention is small, and there was little information available from literature searches, indicating that technology-based suicide prevention remains understudied. Many of the apps provided no interactive features. It is important to verify the accuracy of the results of different apps that are available on iOS and Android. The confidence generated by these apps can benefit end users, either by improving their health monitoring or simply to verify their body condition.